Investigating Quick Speech-in-Noise Comprehension in Adult Bimodal Users - Javad Fakhri; Nematollah Rouhbakhsh; Reza Hoseinabadi; Farzaneh Fatahi; Mahsa Sepehernejad; Zohreh Roghani (Journal of Modern Rehabilitation, 2021)
Introduction: The use of cochlear implants, due to technological limitations, causes problems in speech comprehension in the presence of noise. This study aimed to evaluate the speech-in-noise (SIN) comprehension with emphasis on high-frequency components between users of different bimodal adult. Materials and Methods: This study was conducted on 33 adult participants with a mean age of 36 years using bimodal (cochlear implant in one ear and hearing aid in another ear: CI/HA) style of different companies. Quick SIN with emphasis on high-frequency components was performed on the participants using an audiometer, an amplifier, and one speaker. Results: Comparing the average percentage of correct answers from the word recognition test in the presence of noise in bimodal users showed that the Cochlear brand provides a better signal-to-noise (SNR) compare to other brands. Our result shows that bimodal users of Advance bionic and Med-El groups have better performance in speech recognition than other brands. Conclusion: Bimodal users of Advance bionic and Med-El have better SNR loss than other brands. Besides, further studies on different ages can be helpful to make the right decision in this regard.